Assessment of knowledge on the health risks of noise pollution in schools in the city of Kindu, Maniema province - , MASUMBUKO TEMBEA Lea; PASCAL KIBONGE,; NKAMBA KANKOLONGO Hattie,; SHABANI MACHOZI,; ASSANI WAKENGE Bonny,; MAOLE NGOY Juresse,; NGOY SHABANI Claude,; KALONDA BWANAHALI Gedéon, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Loud noise in schools is one of the environmental problems that is still underestimated and poorly documented. Exposure to these high sound levels is partly responsible for discomfort among teachers and students. The aim of our work was to evaluate the participants' level of knowledge about the effects of noise pollution in schools in the city of Kindu. This was a cross-sectional descriptive study conducted in 60 schools grouped into four main networks in the city of Kindu. The sound level was measured using a REED R 8050 digital sound level meter, providing maximum and minimum values with an accuracy of ± 1.5 dB(A). The survey questionnaire allowed us to collect data on sociodemographic and professional characteristics, knowledge, attitudes, and practices. Regarding the noise level in classrooms, only 2 out of 60 schools (i.e., 3.3%) had a noise level ≤ 40 dB(A). The male sex 258 (or 60.3%) was in the majority, the age category of primary school teachers 118 (or 27.6%) was in the majority. Regarding the sources of noise emissions identified in schools, loud music (75%), playing during recess (73%), and road traffic (60%) constituted the main sources of noise pollution. The level of knowledge of students about health effects was low, only 2 schools out of 60 had a sound level ≤40 dB(A).